Let the Students Map Canadian Studies: Exploring Stereotypes of Canada - Christophe Premat (American Studies in Scandinavia)
This article investigates the perceptions and stereotypes of Canada held by students in Nordic, Scandinavian, and Baltic countries participating in Canadian studies courses. Drawing upon eighty-seven papers submitted between 2021 and 2023, the study employs lexicometric analysis to discern recurring “othering” strategies employed by students. The interdisciplinary nature of the Canadian studies course, blending literature, history, and political science, aims to equip students with the knowledge necessary to examine the nuances of the Canadian social model. By examining cultural stereotypes, the study redefines Canadian studies as an integral component of (North) American studies, highlighting the importance of challenging initial representations and fostering critical thinking. Findings reveal students’ engagement in the process of othering, reflecting on Canadian identity, multiculturalism, and the integration of First Nations. The study underscores the significance of pedagogical interventions in creating spaces for transformation and critical reflection. Ultimately, it demonstrates the potential of area studies to assist students in structuring academic texts and encourages further exploration of themes related to memorial policies and reconciliation in courses on Canadian studies.